ASUPAN ZAT GIZI MAKRO, ZAT BESI DAN ZINK DENGAN KEJADIAN ANEMIA PADA SISWA SEKOLAH MENENGAH PERTAMA NEGERI 3 MANADO - Irza Nanda Ranti; Rivolta G.M. Walalangi (Jurnal GIZIDO, 2014)
Background. Anemia is one health problem worldwide and has a high prevalence in variouscountries around the world. Young women were among those prone to suffer from anemiabecause of menstruation each month and is in its infancy. Anemia most often caused by anemiadeficiency anemia besi.Prevalensi sizeable adolescent girls in adolescence occurs due to rapidgrowth ( growth spurt). The prevalence of anemia in adolescents in North Sulawesi by 3% and thenational average rate of 12.8 % .Research Purpose. This study aims to determine the intake of macro-nutrients ( P, L and KH ) ,iron ( Fe ) and zinc with the incidence of anemia in adolescents aged 12-14 yearsTypes of research.This research is a descriptive survey research crossectional.Populasi in thisstudy were all students of class VIII SMP Negeri 3 Manado totaling 418 students , the samplestaken a number of 41 students were female and willing to become respondents , a sample isobtained using a systematic technique random sampling .Research result. Average protein intake of 69.59 g ( 100.86 % ) good , fat intake of 36.23 g ( 51.02% ) enough , Carbohydrate intake 282.51 g ( 96.75 % ) good , iron intake 5 , 09 mg ( 19.75 % ) isvery low and zinc intake of 6.61 mg ( 41.43 % ) is very low . The conclusion of the 41 respondents, 15 respondents suffer from mild anemia and 26 respondents did not suffer from anemia .